TMS Motor Mapping Methodology and Reliability: A Structured Review - Sondergaard, Rachel E.; Martino, Davide; Kiss, Zelma H. T.; Condliffe, Elizabeth G. (Frontiers in Neuroscience, 2021)
Motor cortical representation can be probed non-invasively using a transcranial magnetic stimulation (TMS) technique known as motor mapping. The mapping technique can influence features of the maps because of several controllable elements. Here we review the literature on six key motor mapping parameters, as well as their influence on outcome measures and discuss factors impacting their selection. 132 of 1,587 distinct records were examined in detail and synthesized to form the basis of our review. A summary of mapping parameters, their impact on outcome measures and feasibility considerations are reported to support the design and interpretation of TMS mapping studies.